Pengaruh Model POGIL terhadap Hasil Belajar dan Kemampuan Berpikir Kritis Siswa SMP - Sudartik Sudartik; Sutarto Sutarto; Aris Singgih Budiarso (UIN Sultan Aji Muhammad Idris Samarinda, 2023)
The ability to think critically is one of the high-level abilities in the 21st century which is very essential to be trained in students through learning activities, one of which is learning science.